if root2=1.414,root3=1.732, then find the value of 4/3root3-2root2+3/3root3+2root2
Answers
Answered by
25
hope it helps!!
ask if any doubts
ask if any doubts
Attachments:
![](https://hi-static.z-dn.net/files/d13/3af13c9df2fc23fe2e192c9354ff9965.png)
Answered by
41
Identity used :
![(x + y)(x - y) = {x}^{2} - {y}^{2} (x + y)(x - y) = {x}^{2} - {y}^{2}](https://tex.z-dn.net/?f=%28x+%2B+y%29%28x+-+y%29+%3D++%7Bx%7D%5E%7B2%7D++-++%7By%7D%5E%7B2%7D+)
Given,
√2 = 1.414
√3 = 1.732
Now,
![\frac{4}{3 \sqrt{3} - 2 \sqrt{2} } + \frac{3}{3 \sqrt{3} + 2 \sqrt{2} } \\ \frac{4}{3 \sqrt{3} - 2 \sqrt{2} } + \frac{3}{3 \sqrt{3} + 2 \sqrt{2} } \\](https://tex.z-dn.net/?f=+%5Cfrac%7B4%7D%7B3+%5Csqrt%7B3%7D++-+2+%5Csqrt%7B2%7D+%7D++%2B++%5Cfrac%7B3%7D%7B3+%5Csqrt%7B3%7D++%2B+2+%5Csqrt%7B2%7D+%7D++%5C%5C+)
On rationalizing the denominator we get,
![= \frac{4}{3 \sqrt{3} - 2 \sqrt{2} } \times \frac{3 \sqrt{3} + 2 \sqrt{2} }{3 \sqrt{3} + 2 \sqrt{2} } + \frac{3}{3 \sqrt{3} + 2 \sqrt{2} } \times \frac{3 \sqrt{3} - 2 \sqrt{2} }{3 \sqrt{3} - 2 \sqrt{2} } \\ \\ = \frac{4(3 \sqrt{3} + 2 \sqrt{2}) }{ {(3 \sqrt{3} )}^{2} - {(2 \sqrt{2} )}^{2} } + \frac{3(3 \sqrt{3} - 2 \sqrt{2} )}{ {(3 \sqrt{3} })^{2} - {(2 \sqrt{2}) }^{2} } \\ \\ = \frac{12 \sqrt{3} + 8 \sqrt{2} }{27 - 8} + \frac{9 \sqrt{3} - 6 \sqrt{2} }{27 - 8} \\ \\ = \frac{12 \sqrt{3} + 8 \sqrt{2} }{19} + \frac{9 \sqrt{3} - 6 \sqrt{2} }{19} \\ \\ = \frac{12 \sqrt{3} + 8 \sqrt{2} + 9 \sqrt{3} - 6 \sqrt{2} }{19} \\ \\ = \frac{21 \sqrt{3} + 2 \sqrt{2} }{19} = \frac{4}{3 \sqrt{3} - 2 \sqrt{2} } \times \frac{3 \sqrt{3} + 2 \sqrt{2} }{3 \sqrt{3} + 2 \sqrt{2} } + \frac{3}{3 \sqrt{3} + 2 \sqrt{2} } \times \frac{3 \sqrt{3} - 2 \sqrt{2} }{3 \sqrt{3} - 2 \sqrt{2} } \\ \\ = \frac{4(3 \sqrt{3} + 2 \sqrt{2}) }{ {(3 \sqrt{3} )}^{2} - {(2 \sqrt{2} )}^{2} } + \frac{3(3 \sqrt{3} - 2 \sqrt{2} )}{ {(3 \sqrt{3} })^{2} - {(2 \sqrt{2}) }^{2} } \\ \\ = \frac{12 \sqrt{3} + 8 \sqrt{2} }{27 - 8} + \frac{9 \sqrt{3} - 6 \sqrt{2} }{27 - 8} \\ \\ = \frac{12 \sqrt{3} + 8 \sqrt{2} }{19} + \frac{9 \sqrt{3} - 6 \sqrt{2} }{19} \\ \\ = \frac{12 \sqrt{3} + 8 \sqrt{2} + 9 \sqrt{3} - 6 \sqrt{2} }{19} \\ \\ = \frac{21 \sqrt{3} + 2 \sqrt{2} }{19}](https://tex.z-dn.net/?f=+%3D++%5Cfrac%7B4%7D%7B3+%5Csqrt%7B3%7D+-+2+%5Csqrt%7B2%7D++%7D++%5Ctimes++%5Cfrac%7B3+%5Csqrt%7B3%7D+%2B+2+%5Csqrt%7B2%7D++%7D%7B3+%5Csqrt%7B3%7D+%2B+2+%5Csqrt%7B2%7D++%7D++%2B++%5Cfrac%7B3%7D%7B3+%5Csqrt%7B3%7D+%2B+2+%5Csqrt%7B2%7D++%7D++%5Ctimes++%5Cfrac%7B3+%5Csqrt%7B3%7D+-+2+%5Csqrt%7B2%7D++%7D%7B3+%5Csqrt%7B3%7D+-+2+%5Csqrt%7B2%7D++%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B4%283+%5Csqrt%7B3%7D++%2B+2+%5Csqrt%7B2%7D%29+%7D%7B+%7B%283+%5Csqrt%7B3%7D+%29%7D%5E%7B2%7D+-++%7B%282+%5Csqrt%7B2%7D+%29%7D%5E%7B2%7D++%7D+++%2B++%5Cfrac%7B3%283+%5Csqrt%7B3%7D+-+2+%5Csqrt%7B2%7D++%29%7D%7B+%7B%283+%5Csqrt%7B3%7D+%7D%29%5E%7B2%7D+-++%7B%282+%5Csqrt%7B2%7D%29+%7D%5E%7B2%7D++%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B12+%5Csqrt%7B3%7D++%2B+8+%5Csqrt%7B2%7D+%7D%7B27+-+8%7D++%2B++%5Cfrac%7B9+%5Csqrt%7B3%7D+-+6+%5Csqrt%7B2%7D++%7D%7B27+-+8%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B12+%5Csqrt%7B3%7D++%2B+8+%5Csqrt%7B2%7D+%7D%7B19%7D++%2B++%5Cfrac%7B9+%5Csqrt%7B3%7D++-+6+%5Csqrt%7B2%7D+%7D%7B19%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B12+%5Csqrt%7B3%7D++%2B+8+%5Csqrt%7B2%7D++%2B+9+%5Csqrt%7B3%7D+-+6+%5Csqrt%7B2%7D++%7D%7B19%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B21+%5Csqrt%7B3%7D+%2B+2+%5Csqrt%7B2%7D++%7D%7B19%7D+)
Putting the values,
![= \frac{21 \times 1.732 + 2 \times 1.414}{19} \\ \\ = \frac{36.372 + 2.828}{19} \\ \\ = \frac{39.2}{19} \\ \\ = 2.06 = \frac{21 \times 1.732 + 2 \times 1.414}{19} \\ \\ = \frac{36.372 + 2.828}{19} \\ \\ = \frac{39.2}{19} \\ \\ = 2.06](https://tex.z-dn.net/?f=+%3D++%5Cfrac%7B21+%5Ctimes+1.732+%2B+2+%5Ctimes+1.414%7D%7B19%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B36.372+%2B+2.828%7D%7B19%7D++%5C%5C++%5C%5C++%3D++%5Cfrac%7B39.2%7D%7B19%7D++%5C%5C++%5C%5C++%3D+2.06)
Given,
√2 = 1.414
√3 = 1.732
Now,
On rationalizing the denominator we get,
Putting the values,
Similar questions